Autonomous and collective sanctions in the international legal order - White, Nigel D. (Brill, 2018)
The UK government is currently proposing the enactment of a “Sanctions Act” upon the UK’s withdrawal from the EU in 2019, embodying a right to impose “autonomous sanctions” against other states and non-state actors, on the basis that the UK will no longer be able to benefit from the EU’s collective sanctioning competence. The spotlight is again on the nature and purposes of sanctions in international law. The article addresses the legal framework applicable to sanctions by, first of all, showing that the nature of sanctions is different in the international legal order to how it is conceived in domestic legal orders in that sanctions are primarily imposed in response to threats to or breaches of the peace and, in so doing, the analysis will distinguish sanctions from countermeasures and other non-forcible measures. It then proceeds to demonstrate that the values of peace and security that underpin sanctions are essentially normative and should be seen as part of the international legal order and enforceable through sanctions alongside other fundamental norms of international law. Whether viewed as responses to breaches of international law or not, the analysis shows that sanctions are collective measures exclusively within the competence of international organizations. Having established the conceptual and legal frameworks for understanding sanctions, the article considers sanctions imposed against states and non-state actors, and explores whether the move towards targeted sanctions is a form of collective response to violations of international law. The article finishes by considering that, in contrast to countermeasures and other measures of self-help, collective sanctions are inherently lawful, but can only be legally justified as measures adopted out of a necessity to prevent major ruptures to peace and international law.